Benzodiazepine overtreatment in status epilepticus is related to higher need of intubation and longer hospitalization. Issue 8 (29th May 2013) - Spatola, Marianna; Alvarez, Vincent; Rossetti, Andrea O.
Summary Benzodiazepine (BDZ), a widely recognized first‐line status epilepticus (SE) treatment, may lead to respiratory depression. This cohort study investigates the effect of BDZ doses in SE patients in terms of morbidity and mortality. It considers incident SE episodes from a prospective registry (2009–2012), comparing patients receiving standard BDZ dose to those receiving exceeding doses (>30% above recommended dose), in terms of likelihood to receive intubation, morbidity, and mortality. Duration of hospitalization was assessed for subjects needing intubation for airways protection (not for refractory SE treatment) versus matched subjects not admitted to the intensive care unit (ICU). We identified 29 subjects receiving "excessive" and 173 "standard" BDZ dose; 45% of the overtreated patients were intubated for airways protection, but only 8% in the standard‐dose group (p < 0.001). However, both groups presented similar clinical outcomes: 50% returned to baseline, 40% acquired a new handicap, and 10% died. Orotracheal intubation due to airways protection was associated with significantly longer hospitalization (mean 2 weeks vs. 1 week, p = 0.008). In conclusion, although administration of excessive BDZ doses in SE treatment does not seem to influence outcome, it is related to higher respiratory depression risk and longer hospitalization, potentially exposing patients to additional complications and costs.